2013
DOI: 10.1016/j.freeradbiomed.2013.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2/ARE-mediated antioxidant actions of pro-electrophilic drugs

Abstract: Living cells maintain a balance between oxidation and reduction, and perturbations of this redox balance are thought to contribute to various diseases. Recent attempts to regulate redox state have focused on electrophiles (EPs), which activate potent cellular defense systems against oxidative stress. One example of this approach is exemplified by carnosic acid (CA) and carnosol (CS), compounds that are found in the herb rosemary (Rosmarinus officinalis). Importantly, CA and CS themselves are not electrophilic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
240
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(251 citation statements)
references
References 104 publications
(357 reference statements)
10
240
0
1
Order By: Relevance
“…Numerous preclinical studies have reported that activation of NRF2 by natural compounds (Satoh et al, 2013) or by disrupting its negative regulator KEAP1 leads to potent anti-inflammatory effects in myeloid leukocytes and macrophages (Lin et al, 2008). In observational studies, a polymorphism in NFE2L2 was associated with reduced transcriptional activity correlating with increased risk of inflammatory bowel disease (Arisawa et al, 2008b) and chronic gastritis (Arisawa et al, 2007).…”
Section: A Key Role Of Nuclear Factor (Erythroid-derived 2)-like 2 Imentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous preclinical studies have reported that activation of NRF2 by natural compounds (Satoh et al, 2013) or by disrupting its negative regulator KEAP1 leads to potent anti-inflammatory effects in myeloid leukocytes and macrophages (Lin et al, 2008). In observational studies, a polymorphism in NFE2L2 was associated with reduced transcriptional activity correlating with increased risk of inflammatory bowel disease (Arisawa et al, 2008b) and chronic gastritis (Arisawa et al, 2007).…”
Section: A Key Role Of Nuclear Factor (Erythroid-derived 2)-like 2 Imentioning
confidence: 99%
“…The majority of known physiologic or pharmacological NRF2 inducers are electrophilic molecules that covalently modify, by oxidation or alkylation, cysteine residues present in the thiol-rich KEAP1 protein (Hur and Gray, 2011;Satoh et al, 2013). KEAP1 is one of the best-suited proteins to act as electrophilic or redox sensor, as it contains 27 cysteine residues in humans and functions as an electrophile trap.…”
Section: A Electrophilic Nuclear Factor (Erythroid-derived 2)-like 2mentioning
confidence: 99%
“…On the other hand, quercetin and quinone rather enhanced the damage to cells. Polyphenol-mediated transition metal redox cycling (enhanced under H 2 O 2 -challenge) or the previously reported interaction with cultured media components might explain this outcome (Lapidot et al 2002;Satoh et al 2013). …”
Section: Ii) Protein Carbonyls Intensitymentioning
confidence: 86%
“…We showed that CA up-regulates endogenous antioxidant phase II enzymes via the NRF2 transcriptional pathway. Moreover, this pathway is largely responsible for the mechanism of CA action because silencing Nrf2 significantly abrogated the protective effect (30,(40)(41)(42)(43). Here, we wanted to determine if CA could provide neuroprotection in the Mef2d +/− mice model of LIRD (44).…”
Section: Carnosic Acid Confers Neuroprotection In Vivo To Light-exposedmentioning
confidence: 99%